Singapore and its Straits, c.1500–1800. Issue 133 (2nd September 2017) - Borschberg, Peter
ABSTRACT: This article provides a synopsis of the history of Singapore and its adjacent straits during the early modern period, spanning from around the fall of Melaka to the Portuguese in 1511, until the founding of the British trading post by Sir Thomas Stamford Raffles in 1819. Attention is focused on five points of general interest: the different maritime arteries known collectively as the Singapore Straits; the (imagined) location of the main island; Johor officials residing on Singapore during the 16th and 17th centuries; the port and settlements located on the southern side of the main island; as well as European visions for fortifying and colonising Singapore before 1800. The arguments show that, far from being a forgotten or neglected place, Singapore as a settlement, port, and strategic location was recognised and appreciated by both the local rulers and the early European colonial powers.